Mucopolysaccharidosis Type I in Mexico: Case-Based Review - Consuelo Cantú-Reyna; Diana Laura Vazquez-Cantu; Héctor Cruz-Camino; Yuriria Arlette Narváez-Díaz; Óscar Flores-Caloca; Óscar González-Llano; Carolina Araiza-Lozano; René Gómez-Gutiérrez (MDPI AG, 2023)
Introduction: Mucopolysaccharidosis type I (MPS I) is a lysosomal storage disease present in 1:100,000 newborns. Variants in the IDUA (alpha-L-iduronidase) gene decrease the enzyme activity for glycosaminoglycans metabolism. MPS I patients exhibit clinical manifestations that fall on the Hurler, Hurler-Scheie, and Scheie syndrome spectrum. Case presentation: We present a male Mexican patient with respiratory exacerbations requiring recurrent hospitalizations. He showed macrocephaly, coarse facies, hepatomegaly, umbilical hernia, and dorsal kyphosis. The sequencing of the IDUA gene revealed the following genotype: c.46_57del12/c.1205G>A. He received combined therapy with hematopoietic stem cell transplantation and enzyme replacement. Mexican case reports were analyzed to estimate the prevalence of the associated genetic variants. Conclusion: Despite the challenges of managing this rare disease in Mexico, our patient benefited from the combined therapy. The discrete clinical manifestations and prompt evaluation by a geneticist were crucial in establishing a diagnosis, enabling an early intervention by a multidisciplinary team. The combination of ERT before and after HSCT provided health benefits to our patient.